(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was conducted on traditional poultry rearing practices and constraints among the tribal villagers in Gohpur, Sonitpur district of Assam. Data were collected from 100 respondents through a semi structured interview schedule. It was found that in case of housing, cent per cent of the respondents provided night shelter and separate house for their birds. Regarding feeding, 80.00 per cent of the respondents were depended on scavenging. In breeding practices, 100.00 per cent of the respondents practised hatching at home under broody hen system. In case of health care only 5.00 per cent of the respondents practised vaccination. In case of managemental practices, cent per cent reported that they took utmost care of their laying hens and provided laying boxes with dry bedding material. The main constraints were high incidence of diseases, non availability of high yielding breed of poultry chicks and high input cost is involved in poultry rearing respectively. Apart from these, lack of scientific rearing practices, lack of timely health care facilities and vaccination facilities and lack of markets for selling birds and eggs were also reported by the respondents.